An Analysis Of Students’ Difficulties In Writing Hortatory Exposition Text At Eleventh Grade Of SMA TAMAN SISWA Pematangsiantar - Anita Purba; Putri Aprilia Kinanti (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2022)
The purpose of this research are to know: 1) The students’ ability in writing Hortatory exposition text at the eleventh grade students of SMA Taman Siswa Pematang siantar in 2021/2022 academic year 2) The difficulties that faced by the students’ in writing Hortatory exposition text at the eleventh grade students of SMA Taman Siswa Pematang siantar in 2021/2022 academic year. This research is used mixed method that is combination of qualitative and quantitative research. This is research was done by using documentation and students text essay hortatory exposition text. The informants of this research are 66 that representative from the eleventh grade students. The data were collected used randomly sampling. Test was made to know the students’ ability in writing Hortatory exposition text and the difficulties that faced by the students’ in writing Hortatory exposition text ability at the eleventh grade, observation was made to know all of the activities or behaviours of the students’ in writing Hortataory exposition text. The highest score 75, the lowest score 38, and the average score in writing Hortatory exposition text 57.33 and it was categorized difficult, it means that students ability in writing Hortatory exposition text are still difficult. The students had difficulty in using content 80%, using organization 73.33%, using vocabulary 73.33%, mastering grammar 93.33%, and using mechanics 20%. It means that the students need to learn more about Hortatory exposition text.while the students difficulties in writing was language features and generic structure of hortatory exposition text consist of thesis and arguments, lack vocabulary and grammar mastery so majority of students was difficult to create the sentences and write correct spelling words, based on the result, the researcher taken a conclusion that the students have not understanding in writing hortatory exposition text